A new Stemonitis species and a new record of Elaeomyxa from China - Bo, Zhang; Yu, Li (Phytotaxa, 2017)
A new species, Stemonitis planusis, was collected in Shennongjia National Nature Reserve, Hubei Province, China; it has larger sporocarps that usually end in a plane at the apex of the sporotheca, and its capillitia are expanded at the axils. Additionally, Elaeomyxa Hagelst. was documented for the first time in China; E. miyazakiensis (Emoto) Hagelst. was identified based on material collected from Dasu Forest, Fushun City, Liaoning Province, China. This newly recorded species is characterised by the wax in its stalk, peridium, and capillitium, and spores (approximately 7–8 μm in diam.) marked with rows of warts. A description and scanning electron micrographs of the collected Elaeomyxa and Stemonitis are provided. All specimens are deposited in the Herbarium of the Mycological Institute of Jilin Agricultural University (HMJAU), Changchun, China.